"A new kind of beast": Assembling the macro-regional collective, the case of the EU BSR-strategy - Jonathan Metzger (European Regional Science Association (ERSA), 2010)
The paper examines the novel governance approach underpinning the European Union Strategy for the Baltic Sea Region (EUSBSR). The EUSBSR was launched in the summer of 2009 and is the first, but perhaps not the last, macro-regional strategy developed by the EU. The strategy does not supply any new instruments, legislation or funding. Instead it collects and highlights diverse and often already existing initiatives and instruments within a Baltic Sea Region framing, adding a macro-regional perspective. In the paper, concepts borrowed from Actor-Network Theory (ANT) are utilized to help us better understand the governance approach behind the strategy. It is argued that the practice of constructing the EUSBSR can be understood as an example of heterogeneous engineering, a performative attempt to assemble a macro-regional collective through translations of interests in processes of problematization, engagement/interessement, enrolment and mobilization. By formulating common matters of concern the idea of common interests is introduced and established. Moreover, the collective that is being assembled in the strategy is clearly hybrid in nature as the strategy attempts to speak for and represent not only the interests of EU member states, but also of entities as diverse as plankton, small businesses and tourists. The paper further discusses the relationship between the governance approach of the EUSBSR and collaborative planning methodology. It is argued that although some aspects of the EUSBSR governance approach are reminiscent of a collaborative approach, the divergences are fundamental.
Keywords: 330